Vulnerable Children and Moral Responsibility: Loss of Humanity. Issue 6 (21st June 2021) - Thayer‐Bacon, Barbara J.
Abstract : In this essay, Barbara Thayer‐Bacon considers the arguments made in favor of "zero tolerance" for immigration at the United States–Mexican border as an example of principled ethics, and she contrasts this position with a caring ethical response. She compares the U.S.'s current zero‐tolerance immigration policy to the zero‐tolerance approach U.S. public schools adopted in response to violence in schools. The zero‐tolerance policies implemented by schools in the wake of several high‐profile incidents serves as a strong illustration of the moral dilemmas that zero‐tolerance policies create generally. Both examples illustrate that zero‐tolerance policies are not an effective moral response to ethical dilemmas; on the contrary, such policies lead to a lack of attention to context, subjectivity, positionality, and institutional power, which in turn generates a range of new and different ethical quandaries. Ultimately, Thayer‐Bacon argues that taking a zero tolerance approach to serious, complicated problems such as immigration policy is misguided; developing fair, humane, caring, and just immigration policies requires a more nuanced approach that attends to the full complexity of the issues involved.